Clinicopathological Features and Prognostic Implication of Gastric Carcinoma with Lymphoid Stroma. (3rd December 2020) - Pyo, Jung-Soo; Kim, Nae Yu; Son, Byoung Kwan; Lee, Hyo Young; Oh, Il Hwan; Chung, Kwang Hyun
Abstract : Background/Objective . Gastric carcinoma with lymphoid stroma (GCLS) has been referred to as lymphoepithelioma-like carcinoma and medullary carcinoma. The present study aims at elucidating the clinicopathologic features and prognostic implications of GCLS through a meta-analysis. Methods . This study included 34 eligible studies and 1757 GCLSs. The clinicopathologic characteristics of GCLS were investigated from eligible studies, and the meta-analysis was performed. In addition, we compared the survival rates between GCLS and non-GCLS. Results . The estimated rate of GCLS was 0.062 (95% confidence interval (CI) 0.040-0.097). GCLS was significantly correlated with the diffuse type of Lauren's classification, proximal tumor location, less-frequent lymphatic invasion, and lower pTNM stage. However, there was no significant difference in age, sex, tumor differentiation, vascular invasion, perineural invasion, pT stage, lymph node metastasis, and distant metastasis between GCLS and non-GCLS patients. EBV positive rates in GCLS and non-GCLS patients were 0.723 (95% CI 0.643-0.791) and 0.064 (95% CI 0.039-0.103), respectively. HER2 expression in GCLS was significantly lower than that in non-GCLS. GCLS patients had a more favorable prognosis than that of non-GCLS patients (hazard ratio 0.500, 95% CI 0.305-0.821). Conclusion . GCLS comprised 6.2% of overall GC and more frequent in the proximal portion of the stomach. Since GCLS was associated with better prognosis, the histologic finding can be useful for predicting the patient's prognosis.